Towards eliminating malaria in high endemic countries: the roles of community health workers and related cadres and their challenges in integrated community case management for malaria: a systematic review. (December 2017) - Sunguya, Bruno; Mlunde, Linda; Ayer, Rakesh; Jimba, Masamine
Abstract Background Human resource for health crisis has impaired global efforts against malaria in highly endemic countries. To address this, the World Health Organization (WHO) recommended scaling-up of community health workers (CHWs) and related cadres owing to their documented success in malaria and other disease prevention and management. Evidence is inconsistent on the roles and challenges they encounter in malaria interventions. This systematic review aims to summarize evidence on roles and challenges of CHWs and related cadres in integrated community case management for malaria (iCCM). Methods This systematic review retrieved evidence from PubMed, CINAHL, ISI Web of Knowledge, and WHO regional databases. Terms extracted from the Boolean phrase used for PubMed were also used in other databases. The review included studies with Randomized Control Trial, Quasi-experimental, Pre-post interventional, Longitudinal and cohort, Cross-sectional, Case study, and Secondary data analysis. Because of heterogeneity, only narrative synthesis was conducted for this review. Results A total of 66 articles were eligible for analysis out of 1380 studies retrieved. CHWs and related cadre roles in malaria interventions included: malaria case management, prevention including health surveillance and health promotion specific to malaria. Despite their documented success, CHWs and related cadres succumb to health system challenges. These are poor and unsustainable finance for iCCM, workforce related challenges, lack of and unsustainable supply of medicines and diagnostics, lack of information and research, service delivery and leadership challenges. Conclusions Community health workers and related cadres had important preventive, case management and promotive roles in malaria interventions. To enable their effective integration into the health systems, the identified challenges should be addressed. They include: introducing sustainable financing on iCCM programmes, tailoring their training to address the identified gaps, improving sustainable supply chain management of malaria drugs and diagnostics, and addressing regulatory challenges in the local contexts.